GLOBAL MUAMMOLARNING MILLIY VA MINTAQAVIY DARAJADAGI YECHIMLARINI TOPISH (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article analyzes global challenges in the context of globalization, their manifestation at national and regional levels, and effective solution mechanisms. Issues such as climate change, environmental crises, food security, migration, poverty, and public health are examined in terms of their impact on sustainable development. The study emphasizes that solving global problems requires not only international cooperation but also strong national policies and regional integration. Conceptual approaches based on the harmonization of national interests and universal values are proposed.